2021
DOI: 10.2196/24196
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Attitudes Toward School Students’ Overuse of Smartphones and Its Detrimental Health Impacts: Qualitative Study

Abstract: Background Parents’ awareness of the risks of the overuse of smartphones (SPs) among their children and parents’ attitudes toward this societal phenomenon are crucial factors to consider when investigating the causes and effects of, as well as interventions to control, this public health issue. Objective This study aimed to explore the awareness and attitudes of parents regarding SP overuse among their children and the detrimental impacts associated wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…While unable to find any studies that cite a parenting knowledge gap in this area, we believe the latter may be explained by the especially close bonding mothers have with young children, which would lead them to be more concerned about smartphone exposure among their offspring. This view is supported by Buabbas et al, 23 who reported that mothers supervised their children's smartphone use more than fathers.…”
Section: Discussionmentioning
confidence: 79%
“…While unable to find any studies that cite a parenting knowledge gap in this area, we believe the latter may be explained by the especially close bonding mothers have with young children, which would lead them to be more concerned about smartphone exposure among their offspring. This view is supported by Buabbas et al, 23 who reported that mothers supervised their children's smartphone use more than fathers.…”
Section: Discussionmentioning
confidence: 79%
“…While many "normal" behaviors not involving the Internet have the potential to become addictive, an emerging body of qualitative research has begun to shed light on how the online world specifically seems to exert a strong compulsion towards constant usage in some young people 26,27,29,[35][36][37][38][39][40][41] . Adolescents express concerns about a "constant stream of entertainment" 41 , affecting critical activities such as homework and sleep 38,41 . Some young people connect their digital behaviors to addiction-like cravings.…”
Section: Endless Engagement In the Online Worldmentioning
confidence: 99%
“…98.3% of parents are agreed that the overuse of mobile phones led to online addiction among their children and which could be side effects of their health like; eye problems, headaches, and anger. Besides, most mothers can't control their children's habits in using mobile phones (Buabbas et al, 2021). Besides that, now focused on the technological connection with religious status.…”
Section: Literature Reviewmentioning
confidence: 99%